Pengaruh Pengawas Minum Obat Tablet Fe Pada Ibu Hamil Yang Anemia Terhadap Kenaikan Hb di Wilayah Kerja Puskesmas Padang Luar Kab. Agam : The Effect of Iron Tablet Consumption Supervision on Anemic Pregnant Women on the Increase of Hemoglobin Levels in the Working Area of Padang Luar Health Center, Agam Regency - Lusina Novita; Wedya Wahyu; Tut Wuri Handayani (NERS Jurnal Keperawatan, 2012)
Anemia is still one of the major health problems in pregnant women in Indonesia. The most common cause of anemia in pregnant women are iron deficient, the impact of iron deficiency in pregnant women can be observed from fetal morbidity and mortality, as well as increased risk of low birth weight. The aim of this study was to determine the effect of Fe tablet medicine supervisor on pregnant women with anemia of Hb increase in work areas of Padang Luar public health center sub province Agam 2012. Design of study was quasi - experiment with "non-randomized control group pretest - posttest design". Samples were taken in Total sampling technique amount to 50 subjects who were divided into two groups, 25 groups of intervention and 25 group of control. In the intervention group involves the family as a supervisor to take medication tablet Fe while in the control group without medication tablet Fe supervisor. Analysis techniques used for the intervention and control groups using the Wilkolson test to see a significant. The statistical test result in intervention and control groups obtained the value p = 0.00 (<0.05). Hence, from the results of this study, there was influence of medication supervision of anemia in pregnant women to increase Hb. It can be concluded that the involvement of family in supervise the medication can improve the obedience of mothers consuming Fe tablets, then increase Hb and decrease anemia incidence.